Temperature coverage simulation of horizontal cylinder type coffee roasting machine. Issue 1 (November 2021) - Fachruddin, F; Syafriandi, S; Fadhil, R
Abstract: This study aims to simulate the temperature distribution of coffee roasting machines and study the profile of coffee beans roasted using a horizontal cylinder-type roaster. The coffee used in this study is arabica. The simulation method for the temperature estimation in the coffee roasting process uses the Solidworks Flow Simulation 2016 software, while the actual temperature measurement using a thermocouple is simulated with the Surfer software version 16. Furthermore, each stage of the coffee roasting process has been carried out, including the weight of the material, the roasting temperature, and the bulk density. The final step is to observe the profile of the roasted coffee beans at every minute of treatment. The study results indicate a difference between the approximate temperature simulation (top 176.85°C, bottom 191.97°C) and the actual temperature measured results (upper 214°C, bottom 220°C). The weight of the material (coffee green bean), the roasting temperature, and the bulk density during the test experienced regular movements from the beginning to the end of the treatment. The profile of roasted coffee beans shows a darker color movement along with the longer roasting time used. The profile of the roasted coffee beans will be beneficial in determining at which level of roasting you want (light, medium, medium-dark, dark).